FIGHTING CLASSROOM BOREDOM: INNOVATIVE ACTIVE LEARNING MODELS TO ADDRESS STUDENT MOTIVATION CHALLENGES IN ELEMENTARY SCHOOLS A LITERATURE STUDY WITH CASE SIMULATIONS AT A PRIMARY SCHOOL IN NABIRE - Desi Handayani Duapadang; Lusia Narsia Amsad; Yan Dirk Wabiser; Bryan Tumeno (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Boredom in the learning process at elementary schools (SD) is a significant factor in declining student motivation and academic achievement. In regions with unique geographical and cultural characteristics, such as Papua, this challenge is often exacerbated by the limitations of conventional learning media and teaching methods, which tend to be monotonous. This research aims to analyze the effectiveness of active learning model innovation as a strategic solution to increase elementary school students' learning motivation. The research method used is library research by analyzing literature from the last 10 years and integrating observational case studies from an elementary school in Nabire, Papua. The results show that the implementation of Game-Based Learning and Outdoor Collaborative Learning models can significantly reduce student boredom levels. The case in Papua shows that the use of local wisdom (ethno-pedagogy) as part of active learning increases student engagement by up to 50%. Analysis of literature data confirms that physical and emotional involvement in learning strengthens memory retention and intrinsic interest. The conclusion of this research affirms that teachers must transform from information providers to creative facilitators to create a dynamic classroom ecosystem. The proposed solutions include diversifying activity-based methods and adapting environment-based curricula to ensure the sustainability of children's learning motivation at the elementary education level.